2014
DOI: 10.3126/ajms.v6i1.10799
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical changes in some trace elements, antioxidant vitamins and their therapeutic importance in prostate cancer patients

Abstract: Aim: This study was conducted to evaluate the serum levels of some trace-elements (zinc, copper and selenium) and antioxidant vitamins (vitamin A, C and E) in prostate cancer patients. Method: A total of 50 prostate cancer patients aged 50-70 years with PSA > 4.0 ng/dl were recruited for the study while 50 apparently healthy individual were used as control subjects. Zinc, copper and selenium were determined using atomic absorption spectrophotometer while vitamin A, C and E were determined using high performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 11 publications
1
13
1
Order By: Relevance
“…Evidence suggests that environmental factors acting in concert with genetic influences could be responsible for PCa severity which usually determines the disease progression [89101112]. Low zinc status is one environmental factor that has been implicated to play a role in prostate carcinogenesis and its severe variants which define the disease progression [1112].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence suggests that environmental factors acting in concert with genetic influences could be responsible for PCa severity which usually determines the disease progression [89101112]. Low zinc status is one environmental factor that has been implicated to play a role in prostate carcinogenesis and its severe variants which define the disease progression [1112].…”
Section: Introductionmentioning
confidence: 99%
“…This finding contradicts other studies on the association of trace elements and some vitamins with prostate disorders. 2,3,[14][15][16] On the other hand, a significant increase in the serum level of Vit A was observed in the prostatic cancer group compared to the control with other vitamins and trace elements showing no significant difference which negates the reports of other previous similar studies. 3 Furthermore, PSA is observed to be positively correlated with trace elements and vitamins in the control subjects.…”
Section: Discussionmentioning
confidence: 89%
“…2,3,[14][15][16] On the other hand, a significant increase in the serum level of Vit A was observed in the prostatic cancer group compared to the control with other vitamins and trace elements showing no significant difference which negates the reports of other previous similar studies. 3 Furthermore, PSA is observed to be positively correlated with trace elements and vitamins in the control subjects. Vitamin A, its natural and synthetic analogs have been reported to enhance prostate cancer risks and it is remarkable that the BPH group investigated in this study showed positive correlation of PSA with vitamin A.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations